Determinants of stock market returns in emerging markets: The linkage between institutional quality and macro liquidity. (13th December 2020) - Nguyen, Canh P.; Schinckus, Christophe; Su, Thanh D.; Chong, Felicia H. L.
Abstract: This article identifies that the institutional framework of a country and its liquidity are the main key drivers of stock market returns. To study this, we used the worldwide governance indicators as proxies to measure institutional quality. We apply the Sys‐GMM to model the correlational relationship of our variables. Our analysis for both institutional quality and macro liquidity in this study differs from the mainstream literature. In this paper, we modelled the stock market returns by adding the quality of a country's institutional framework and the country's liquidity level (measured by M2 account of money supply) to redefine classical models found in the mainstream literature. Sys‐GMM is applied for a panel of 34 emerging countries between 2002 and 2013. We observed an excess of liquidity for the country's level positively affects stock market returns in these countries. This positive influence is actually enhanced through the development of an adequate institutional framework. In this context, a high national liquidity volatility, as it is often observed in emerging countries, is not necessarily a bad thing for the financial markets and their influence can actually be enhanced through an adequate institutional structure to promote long‐term wealth for the society's well‐being and not only the wealth resulting from temporary capital market returns.